PERAN MANAJERIAL KEPALA SEKOLAH DALAM MEINGKATKAN KUALITAS KINERJA GURU PADA KEGIATAN PEMBELAJARAN TATAP MUKA TERBATAS DI SD NEGERI SAGA I KABUPATEN TANGERANG - Putri Puji Lestari; Yuyu Yuhana; Reksa Adya Pribadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
The purpose of this research is to provide an overview of the planning, implementation and output of the principal's program which involves the managerial role of the principal in the school to improve the quality of teacher performance. Creating a school that has good quality is the principal's job, creating a fun learning experience is the teacher's job and getting a meaningful learning experience is the dream of students. This study uses a descriptive qualitative method by looking at the actual situation as a whole. The results of this study indicate that the process of implementing the program from planning to getting the output was successful by the school principal in view of the existence of schools that have increased quality, the ability of teachers to continue to increase in carrying out learning in class, the presence of students who have character.